Checklist of medicinal plants used by traditional women for maternal health care in Lagos State, Nigeria - Sharaibi, O. J.; Oluwa, O. K.; Omolokun, K. T.; Ogbe, A. A.; Adebayo, A. O. (Journal of Medicinal Herbs and Ethnomedicine, 2024)
Traditional women in Lagos State, Southwest, Nigeria have been using medicinal plants for maternal health care since time immemorial. However, there is no proper documentation of medicinal plants used in maternal health care, as information is passed from generation to generation orally. This study aimed at the identification and documentation of medicinal plants used in Lagos, Nigeria for maternal health care. Ethnobotanical studies were carried out in six local government areas namely, Agege, Alimosho, Badagry, Ejigbo, Mushin and Ojo. A Semi-structured questionnaire was designed to obtain information from 300 respondents, 50 from each local government area. The respondents included herbal merchants, herbal medicine practitioners, midwives, and traditional birth attendants. Information obtained included the names of the plants, plant parts used, mode of preparation and administration and dosage of the medicinal herbs. Forty-five (45) plants belonging to twenty-three (23) families were identified and documented in the study area. Most of the reported plants belong to the Fabaceae (13.52%), Malvaceae (8.41%) and Annonaceae (6.67%) families. Kigelia africana, Caliandra portoricensis, Nauclea latifolia and Securidata longepedunculata had the highest Relative Frequency of Citation (RFC) and Fidelity Level (FL) of 0.96; 100% and 0.82; 100%, 0.92; 100 % and 0.78; 100% respectively. Most of the reported plants (73.47%) were herbs and shrubs and about 62.68% of the surveyed plants were wild. Leaves were the most frequently used (72.74%) plant’s part. Most of the herbs (80.45 %) were prepared as decoctions and preparations were mostly administered orally (88.64%). Strategies suggested to conserve the surveyed plants include the cultivation of medicinal plants to prevent their extinction.